806 The Efficacy of Prostatic Arterial Embolisation as Indicated by Clinical Outcomes. (19th August 2022) - Parmar, S; McRae, B; Hines, J; Munneke, G; Walkden, M; Von Stempel, C
Abstract: Aim: PAE (prostatic arterial embolisation) is a non-surgical, minimally invasive procedure used to treat symptoms of benign prostatic hyperplasia (BPH). It is used to treat patients with moderate to severe lower urinary tract symptoms including those requiring long term urinary catheter placement and intermittent self-catheterisation. The incidence of urinary tract infection is greater in this group at baseline and the risk of infection as a complication of PAE is recognised in the literature. This study aimed to compare the clinical outcomes of PAE to those of TURP (transurethral resection of the prostate), the reference standard for BPH treatment. Method: All patients who underwent PAE between 2019 to 2021 at a single centre were included in this retrospective study. Clinical outcomes of patients were also recorded including international prostate symptom score (IPSS) and urodynamic results. These were compared to TURP results provided in the UK ROPE study. Results: 82% of patients experienced an improved IPSS after PAE, with a median reduction of 15 points, compared with a median reduction of 17 points with TURP. PAE caused a greater reduction in median prostate volume but proved to be less effective in improving urodynamic test results when compared to TURP. Conclusion: While still clinically effective, PAE is less effective for treatment of lower urinary tract symptoms from BPH when compared to TURP.